Integration of Adlerian Play Therapy in Pediatric Hospitals. Issue 1 (2nd January 2019) - Russell, Bethany; Oh, Seungbin; Dillman Taylor, Dalena
Abstract : The multifaceted challenges faced by children with chronic illnesses illuminate a need for additional supports focusing on this population's mental health. Although child life (CL) services and specialists support the immediate needs of the children, there is still an absence of resources to serve the long-term mental health needs of children with chronic illnesses. Adlerian play therapy (AdPT), an evidence-based intervention, is a developmentally responsive approach to counseling children and is compatible with hospital settings. This article provides guidelines for integrating AdPT into the existing system through the guidance of the pediatric medical traumatic stress (PMTS) model.